2019
DOI: 10.3390/ijms20163862
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Neurological Disorders with Human Pluripotent Stem Cell-Derived Astrocytes

Abstract: Astrocytes play vital roles in neurological disorders. The use of human induced pluripotent stem cell (iPSC)-derived astrocytes provides a chance to explore the contributions of astrocytes in human diseases. Here we review human iPSC-based models for neurological disorders associated with human astrocytes and discuss the points of each model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…However, GFAP is not expressed in all mature human astrocytes [ 121 , 122 ]; therefore, a panel of additional astrocyte markers including S100-beta and NDRG2 [ 120 , 123 ] is recommended to confirm astrocyte identity prior to use. Sources of human astrocytes include commercial immortalized (astrocytoma) cell lines [ 124 , 125 , 126 ] and primary cells [ 127 , 128 , 129 ], as well as a growing collection of published protocols to generate iPSC-derived astrocytes, [ 130 , 131 , 132 , 133 ] as reviewed in [ 134 , 135 , 136 ]. Several new differentiation protocols have been published within the last year, including Gatto et al who showed that direct differentiation of astrocytes from fibroblasts retained the age-related transcriptional differences of their donors [ 137 ].…”
Section: Decision Workflow: Factors To Consider When Selecting a Model Systemmentioning
confidence: 99%
“…However, GFAP is not expressed in all mature human astrocytes [ 121 , 122 ]; therefore, a panel of additional astrocyte markers including S100-beta and NDRG2 [ 120 , 123 ] is recommended to confirm astrocyte identity prior to use. Sources of human astrocytes include commercial immortalized (astrocytoma) cell lines [ 124 , 125 , 126 ] and primary cells [ 127 , 128 , 129 ], as well as a growing collection of published protocols to generate iPSC-derived astrocytes, [ 130 , 131 , 132 , 133 ] as reviewed in [ 134 , 135 , 136 ]. Several new differentiation protocols have been published within the last year, including Gatto et al who showed that direct differentiation of astrocytes from fibroblasts retained the age-related transcriptional differences of their donors [ 137 ].…”
Section: Decision Workflow: Factors To Consider When Selecting a Model Systemmentioning
confidence: 99%
“…The comprehensive work carried out in the field of pluripotent stem cells over the past decade has led to the development of numerous protocols for generating hiPSCs, producing neurons, glia and many other cell types from them, as well as enhanced conditions for in vitro culture (Figure 4) (Roybon et al, 2013;Sances et al, 2016;Tao and Zhang, 2016;Gonzalez et al, 2017;Costamagna et al, 2019;Logan et al, 2019;Savchenko et al, 2019;Suga et al, 2019;Karagiannis and Inoue, 2020;Li and Shi, 2020). Even though we still lack a comprehensive knowledge on the survival requirements of human MNs in vitro, patient-specific MNs can still be used to gain insights into the underlying mechanisms of ALS and to perform screenings to identify drug candidates (Figure 3).…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…More advanced protocols were able to overcome this drawback and reduce differentiation time to as little as 30 days by using NPCs as a starting point [ 112 , 113 ]. Detailed descriptions of differences and commonalities between published astrocyte differentiation protocols are described elsewhere [ 113 , 114 ]. Before the start of glial differentiation, iPSC must pass a neuronal progenitor phase.…”
Section: Astrocytes In Health and Diseasementioning
confidence: 99%